Analisis Pengaruh Kepercayaan Konsumen, Kemudahan Penggunaan, Dan Keamanan Transaksi Terhadap Keputusan Pembelian Secara Online Pada Tiktok Shop - Mandiar, Azhiris; M. Haiqal Rafli Rauf; Yocky Pramudya Ananda (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to analyze the influence of consumer trust, ease of use, and transaction security on purchasing decisions on TikTok Shop by Generation Z consumers. This study used a quantitative approach, collecting data through distributing questionnaires to 100 respondents who are active TikTok Shop users. The sampling technique used was non-probability sampling with a purposive sampling approach. Data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results showed that consumer trust and transaction security had a positive and significant influence on purchasing decisions, while ease of use had no significant influence. These findings emphasize the importance of enhancing security and trust in shaping consumer purchasing decisions online.